2012
DOI: 10.1126/science.1214680
|View full text |Cite
|
Sign up to set email alerts
|

MARF1 Regulates Essential Oogenic Processes in Mice

Abstract: Development of fertilization-competent oocytes depends on integrated processes controlling meiosis, cytoplasmic development, and maintenance of genomic integrity. We show that meiosis arrest female 1 (MARF1) is required for these processes in mammalian oocytes. Mutations of Marf1 cause female infertility characterized by up-regulation of a cohort of transcripts, increased retrotransposon expression, defective cytoplasmic maturation, and meiotic arrest. Up-regulation of protein phosphatase 2 catalytic subunit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 30 publications
4
104
0
Order By: Relevance
“…18,19 In our study, the loss of PP2Acs did not significantly affect GVBD kinetics in oocytes under normal culture condition. It is worth determining whether DKO oocytes exhibit altered GVBD kinetics under challenging conditions.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formamentioning
confidence: 46%
See 2 more Smart Citations
“…18,19 In our study, the loss of PP2Acs did not significantly affect GVBD kinetics in oocytes under normal culture condition. It is worth determining whether DKO oocytes exhibit altered GVBD kinetics under challenging conditions.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formamentioning
confidence: 46%
“…Previous studies have shown that PP2A can inhibit GVBD in mouse oocytes. 18,19 We found that DKO oocytes showed indistinguishable GVBD kinetics compared to Ctrl oocytes when they were cultured in M2 medium (Fig. 1B).…”
Section: Stimulation (Supplementary Informationmentioning
confidence: 87%
See 1 more Smart Citation
“…Setdb1-mediated H3K9me3 and DNA methylation have been implicated in the silencing of LTR elements in undifferentiated and differentiated cells, respectively (Hutnick et al, 2010;Matsui et al, 2010;Walsh et al, 1998). Setdb1 controls H3K9me3 deposition at and silencing of several class I ERV1 and class II ERVK retrotransposons in ESCs, PGCs and in Milrinone and Rp-cAMP are inhibitors of PDE3A and PKA, respectively (modified from Su et al, 2012). (C) Percentage of GVBD at 2 h and 18 h after milrinone removal for oocytes treated with or without Rp-cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Like Oskar, the proteins TDRD5, TDRD7, and MARF1 play critical roles in germ cell development in animals, but their molecular function is not known. In mice, MARF1 is oocyte-specific and required for meiotic progression, and MARF1 mutant mouse females are sterile (Su et al 2012). In contrast, mammalian TDRD5 and TDRD7 have important roles during spermatogenesis, and TDRD5-or TDRD7-deficient males are sterile (Lachke et al 2011;Tanaka et al 2011;Yabuta et al 2011).…”
mentioning
confidence: 99%